Choice of transport mode in emerging adulthood: Differences between secondary school students, studying young adults and working young adults and relations with gender, SES and living environment. (September 2017) - Simons, Dorien; De Bourdeaudhuij, Ilse; Clarys, Peter; de Geus, Bas; Vandelanotte, Corneel; Van Cauwenberg, Jelle; Deforche, Benedicte
Highlights: Differences in walking, cycling, car use and public transport use were examined. 1307 emerging adults (17–25 yrs) completed an online questionnaire. Men were more likely to cycle but less likely to commute by car than women. Working young adults were least likely to use active and public transport. Working young adults were most likely to travel by car among the three groups. Abstract: Background: Encouraging sustainable travel behavior in emerging adults is important because this transport choice might persist into adulthood. However, research on transport habits in emerging adulthood is scarce. This study aimed to examine potential differences in walking, cycling, car use and public transport use between three groups of emerging adults (secondary school students (17–18 yrs), studying young adults (18–25 yrs) and working young adults (18–25 yrs)), and to investigate differences in choice of transport modes within each of the three groups according to gender, SES and living environment. Methods: A cross-sectional design was used to collect self-reported data via an online survey that assessed socio-demographic variables, commuting (to work or school) and transport to other destinations. 1307 emerging adults completed the questionnaire. Zero-inflated negative binomial regression models were used. The four dependent variables were minutes per week walking, cycling, car use and public transport use. Results: Compared to the other two groups, secondary school students were most likely to cycle, studying young adults were most likely to walk and use public transport and working young adults were most likely to use a car. In each of the three groups, men were more likely to cycle than women and women were more likely to commute by car to work/school than men. Female secondary school students were also more likely to use a car to other destinations. In each of the three groups, urban emerging adults were more likely to walk and less likely to use a car than those living in rural areas. Urban studying young adults were more likely to cycle to other destinations and urban working young adults were more likely to cycle to work than their rural counterparts. Urban secondary school students were less likely to use public transport to school, although urban studying young adults and working young adults were more likely to use public transport than their rural counterparts. In each of the three groups, high SES emerging adults were more likely to travel by car to other destinations than those with low SES. Conclusions: Future active transport interventions should focus on female emerging adults and on maintaining the habit of cycling after reaching the age at which it is possible to obtain a driver's license. More research on the travel behavior of working young adults is needed as this often neglected target group was least likely to use active and public transport and most likely to travel by car among the three comparison groups. Encouraging the combined use of active and public transport might help to decrease car use when travelling longer distances.